2018
DOI: 10.1175/jcli-d-17-0229.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Subtropical High and Storm Track on Low-Cloud Fraction and Its Seasonality over the South Indian Ocean

Abstract: The south Indian Ocean is characterized by enhanced midlatitude storm-track activity around a prominent sea surface temperature (SST) front and unique seasonality of the surface subtropical Mascarene high. The present study investigates the climatological distribution of low-cloud fraction (LCF) and its seasonality by using satellite data, in order to elucidate the role of the storm-track activity and subtropical high. On the equatorward flank of the SST front, summertime LCF is locally maximized despite small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 82 publications
(118 reference statements)
6
55
0
Order By: Relevance
“…Several recent studies have demonstrated the utility of cloud controlling factor analyses for understanding changes in extratropical low‐level cloud properties. These include Gordon and Klein () and Terai et al () for cloud optical depth, Ceppi et al () for liquid water path (LWP), Grise and Medeiros () and Kelleher and Grise () for SWCRE, and Zelinka et al () and Miyamoto et al () for low cloud cover (LCC). Encouraged by these studies, we apply CCF analysis to estimate how LCC and in‐cloud LWP for low clouds (LWP low) depend on five CCFs in the piControl simulations.…”
Section: Resultsmentioning
confidence: 99%
“…Several recent studies have demonstrated the utility of cloud controlling factor analyses for understanding changes in extratropical low‐level cloud properties. These include Gordon and Klein () and Terai et al () for cloud optical depth, Ceppi et al () for liquid water path (LWP), Grise and Medeiros () and Kelleher and Grise () for SWCRE, and Zelinka et al () and Miyamoto et al () for low cloud cover (LCC). Encouraged by these studies, we apply CCF analysis to estimate how LCC and in‐cloud LWP for low clouds (LWP low) depend on five CCFs in the piControl simulations.…”
Section: Resultsmentioning
confidence: 99%
“…The Mascarene High is a zone of high pressure located on average between 25°S and 35°S and between 40°E and 90°E in austral winter. It is strongest in austral winter but exists all the year round, and moves eastward in austral summer (Lee et al ., ; Miyamoto et al ., ).…”
Section: Seasonal Cloud Distribution Over the Southwest Indian Oceanmentioning
confidence: 99%
“…a–b in Miyamoto et al . (). In region B2, the monthly averaged warm liquid cloud occurrence in July and August is 36% (relatively to all footprints) and 62% (of all clouds) (not shown); warm clouds predominate in winter.…”
Section: Seasonal Cloud Distribution Over the Southwest Indian Oceanmentioning
confidence: 99%
See 2 more Smart Citations